POLITICS AS A SOCIAL PHENOMENON IN THE CONTEXT OF ANTHROPOLOGY - Obidova Ruxshona (Modern American Journals, 2025)
This article discusses the concepts of politics and anthropology, their meanings, and the areas they cover. It also briefly outlines the role and significance of politics in the social life of society. The main content of the article demonstrates how politics can be considered a social phenomenon within the context of the science of anthropology.
Keywords: Politics, anthropology, social, society, science, governance.